Students’ Perceptions in the Use of Web-Based Character Assessment: A View from Gender Perspective - Darmaji, Darmaji; Astalini, Astalini; Kurniawan, Dwi Agus; Aldila, Febri Tia (FKIP Universitas Lampung, 2021)
Perceptions in the Use of Web-based Character Assessment from Gnder Perspective. Objectives: the purpose of this study is to determine the perception of the use of web characters based on gender differences. Methods: This study uses a quantitative method with a survey approach. Participants were eighth grade students of SMPN 6 Batanghari with a sample of 140 students. The data collection technique used a student perception questionnaire. Data analysis used descriptive statistics and inferential statistics in the form of t-test. Findings: The results of the study found that the value of Sig. (2-tailed) female students in grades A and B were 0.031 and 0.020 while the value of Sig. (2-tailed) male students in grades A and B are 0.033 and 0.021. Female students reported to have better perceptions than male students. Conclusion: Students have varied perceptions about web-based character assessment and female students’ perception is better than others. Keywords: Perceptions, web-based assessment, character, gender DOI: 10.23960/jpp.v11.i2.202117